"LOVE" CONCERT AS AN IMPORTANT ELEMENT OF THE LANDSCAPE OF THE EMOTIONAL WORLD (Scientific journal of the Fergana State University, 2024)
One of the central concepts of any culture is the concept of love. Love, that is, love, is a unique event-phenomenon related to people. Its uniqueness lies not only in existence "outside of time", but also in globality, because love is a universal and individual feeling, as noted above. According to the researchers, a single concert cannot cover as much meaning and broad cultural features as the emotional concert of "love". The concert "Love" is the main universal concept that is reflected in any language. From this point of view, researchers give different interpretations of this emotional concert.